Use of comics for teaching Medical English Purpose - Gutierrez Huancayo, Vladimir Román (Technium Social Sciences Journal, 2021)
The main aim of this research was to demonstrate the effectiveness of the comics in teaching English for Medical Purpose (EMP) to students of Medicine in a public University in Peru. For said effect, was used a mixed-method, because in the first and last part, was obtained quantitative data from pre and post-test, both of them, designed for measuring written and oral skills in EMP. These numerical findings served for establishing the proficiencies in both skills, for this reason, this research has also a qualitative component. In the aftermath of the pre-test, the students took seventeen lessons, whereby were they learned fundamental health topics. Consequently, the students in groups of five completed the worksheet consisting of comics created by the author of this paper. Each worksheet had empty bubbles, thereby, the students could create a story, when they filled those bubbles. The stories created by the students served for assessing the written skills, after that, each group was represented in role-playing the story created, this last activity served for assessing the oral skills. In the last part, the students answered the post-test. It was notorious the different results in both test findings, therefore was demonstrated that the effectiveness of using comics in teaching EMP was evident, in the other side this research reaffirms the usefulness of comics in the teaching-learning English process.